Analisis Gaya Kepemimpinan Transformasional terhadap Motivasi Kerja Karyawan pada PT Metric Medica - Harmen, Hilma; Hartono, Dafin; Lumbantoruan, Putri Anita; Amalia, Indry; Silaen, Cindy Lastiur; Gultom, Aenisyah Putri Larasati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The healthcare industry is experiencing rapid transformations due to technological advancements, demographic shifts, and regulatory changes, which create challenges in maintaining employee motivation. This study aims to analyze the influence of transformational leadership style on employee work motivation at PT Deca Metric Medica, a medical device manufacturing company in Indonesia. A qualitative literature review approach was applied by synthesizing academic journals, books, and research articles related to transformational leadership and work motivation. The findings reveal that transformational leadership plays a significant role in inspiring, guiding, and motivating employees through four dimensions: inspirational motivation, idealized influence, intellectual stimulation, and individualized consideration. These dimensions are found to strengthen employee engagement, foster creativity, and enhance job satisfaction, thereby supporting organizational performance in a dynamic healthcare environment. The study concludes that adopting transformational leadership is an effective strategy for PT Deca Metric Medica to sustain employee motivation and competitiveness. However, as this research is based on literature review, future empirical studies are recommended to validate the findings in organizational contexts.